JAVAANSCHE PADVINDERS ORGANISATIE DI MANGKUNEGARAN (1916-1942) - Pujiartati, Renny; Joebagio, Hermanu; Isawati, Isawati (Candi, 2016)
The aims of the research are to identifity: (1) the background of the establishment of the Javaansche Padvinders Organisatie (JPO) in Mangkunegaran; (2) the development of the JPO in Mangkunegaran (1916-1942); and (3) the role of the JPO, which has been done in the field of social, political, and cultural.Research methodology that used is Historical method. The historical method is the process of critically examine and analyze records and relics of the past. The initial phase of the method of historical research is to collect data or heuristics. The research data were collected in the form of primary and secondary sources, consisting of archives, magazines, and books related to the JPO. The instrument used to collect the data in the form of a human instrument, in which the researcher herself. After the data collection was completed, a data analysis was conducted. In analyzing the data, the researcher verified or criticized, interpreted, and then explained the historiography.Based on the research result, it can be concluded: (1) the establishment of JPO was caused by two factors: external and internal factors. External factors derived from the development of the world scouting movement towards the establishment of the JPO and internal factors derived from the socio-political conditions faced by Mangkunegoro VII at the beginning of his reign; (2) the development of the JPO is divided into three periods. In 1916-1923 was an early period, so that the JPO was difficult in recruiting members. In 1924-1938 was a JPO progression period, in 1937 the JPO already has 28 branches with 6,000 members. In 1929-1942 was a period of the decline of JPOthen dissolved by the Japanese in 1942; (3) the JPO has an important role in the social, political, and cultural. The role of JPO in the social field is as a container and an instrument in preparing physically and mentally of the members to face the social life of its members in the future. Politics, JPO performs political activities to show that Mangkunegoro VII has the power, authority, influence and great power in politics. JPO?s role in the field of culture and arts education. JPO is used as containers to educate and lead children, especially in terms of the formation of personality and body work in order to be useful and valuable population. In the arts, JPO actively teaches Javanese art especially palace Mangkunegaran to its members and to the subjects Mangkunegaran in general.